On correlation of rheological, thermal, mechanical and morphological properties of chemical assisted mechanically blended ABS-Graphene composite as tertiary recycling for 3D printing applications. Issue 3 (3rd July 2022) - Kumar, Vinay; Singh, Rupinder; Ahuja, I.P.S.
ABSTRACT: In past two decades, numerous 3D printing applications of acrylonitrile butadiene styrene (ABS) based mechanically blended composites for secondary (2°) recycling has been reported. But hitherto little has been reported on correlation of rheological, thermal, mechanical and morphological properties of chemical assisted mechanically blended ABS-Graphene (Gr) composite as tertiary (3°) recycling. In the present work chemical assisted mechanical blending of ABS and Gr nano particles (size 5–10 nm in three different weight proportions i.e. 10, 15 and 20%) has been reported. The effect of increasing Gr proportion was studied for establishing the correlation among rheological (melt flow index (MFI)) and viscosity), thermal, mechanical and morphological properties. The results of the MFI and viscosity testing showed that 20%Gr in ABS decreases the MFI and increases the viscosity of the composite matrix. The thermal testing showed that ABS+20%Gr composite have highest heat capacity (0.84 j/g) among selected proportions of matrix. As regards to mechanical properties are concerned, best settings are: ABS+20%Gr, temperature 210°C with 0.5 Nm torque for filament wire preparation on twin screw extruder (TSE). Morphological properties of filament wires were studied on metallurgical microscope to observe porosity percentage (%) in wire samples which was found minimum for ABS+20Gr.